Histopathologic differences between adult and pediatric patients with chronic rhinosinusitis. Issue 1 (13th July 2022) - Brown, Hannah J.; Khalife, Sarah; Ganesan, Veena; Escobedo, Pedro; Filip, Peter; Jeffe, Jill; Karas, Anatoli; Papagiannopoulos, Peter; Gattuso, Paolo; Batra, Pete S.; Tajudeen, Bobby A.
Abstract: Background: Adult and pediatric patients with chronic rhinosinusitis (CRS) may have differing philosophies in therapeutic management. Few studies have examined sinonasal tissue‐level comparisons of these groups. This study examines histopathologic differences between children and adults with CRS, with the goal of understanding disease pathogenesis and optimizing medical management for both populations. Methods: In a retrospective cohort of CRS patients who underwent functional endoscopic sinus surgery (FESS), demographic factors, pertinent comorbidities, and a structured histopathologic report of 13 variables were compared across pediatric and adult CRS patients with and without nasal polyps (pCRSwNP, pCRSsNP, aCRSwNP, aCRSsNP, respectively). Results: A total of 378 adult (181 aCRSsNP, 197 aCRSwNP) and 50 pediatric (28 pCRSsNP, 22 pCRSwNP) patients were analyzed. Significantly more children compared with adults had a comorbid asthma diagnosis (64.5% vs. 37.2%, p = 0.003 ). Adults with CRS exhibited significantly more tissue neutrophilia (28.9% vs. 12.0%, p = 0.006 ), basement membrane thickening (70.3% vs. 44.0%, p <   0.001 ), subepithelial edema (61% vs. 30.0%, p <   0.001 ), squamous metaplasia (22.0% vs. 4.0%, p <   0.001 ), and eosinophil aggregates (22.8% vs. 4.0%, p <   0.001 ) than children with CRS. The majority (66.5%) of adult CRS patients exhibited a lymphoplasmacytic‐predominant inflammatory background, whereas the majority (57.8%) of children with CRS exhibited a lymphocyte‐predominant inflammatory background. Conclusions: Sinonasal tissue of adult and pediatric CRS patients demonstrates clear histopathologic differences. Our findings provide insight into differing pathophysiology, which may enable optimization of targeted therapies for patients in each of these unique clinical groups.